THE TRADEMARK POSTULATE BY ADV. PRERNA TYAGI - JEFFERSON, THOMAS (Trinity Law Review, 2023)
Trademarks are a subtype of Intellectual Property typically pertaining to marks that may be graphically displayed and can identify one's goods or services from the goods or services of others. The owner of a trademark, like the owner of any other tangible or intangible property, can transfer the rights he has by renting or assigning them to whomever. This can be related to the quote stated above. The most efficient techniques of commercialization are trademark assignment and licencing, which are commonly used by intellectual property owners. These properties can make use of the transfer of rights in the same way that they can make use of consideration in the form of royalties and other kinds of trade. This article highlights the novel concepts of IPR and focuses on laws relating the field by touching the basic lines of infringement.
Keywords: TRADEMARK; POSTULATE; ADV. PRERNa